The Image of the Dervish in the Poetry of Parvin Etesami: the Spiritual Ideal of the Poet - T. A. Koshemchuk; M. L. Reysner (Концепт: философия, религия, культура, 2023)
The article analyzes the image of a dervish, a character of traditional Sufi lyrics and didactics, that is a key image for poetry by Parvin Etesami (1907-1941). In the only collection of the poet published in literary translation in Russian (The Journey of the Tear, 1984), Sufi motives are almost not revealed. On the basis of new philological translations, the article analyzes the spiritual ideal of the poet, her reflections on the path to the Truth, which she trusts to her beloved hero – a sage, ascetic, dervish, a guide to the knowledge of God. The paper reveals the medieval origins of the image of the dervish of Parvin Etesami, its connection with the Persian classical poetry of the religious and didactic direction, as well as the reasons for the extraordinary stability of the motives grouped around the image of the dervish. On the example of poems of different genre forms (masnavi, monazere, kasida), in which this image is present (or its substitutes — a sage-mystic, a madman, a beggar), its conceptual role for Parvin Etesami is shown. The image of the dervish, in its two hypostases deployed in the Persian classics, appears original in her poems: the dominant features of the dervish are ascetic, mystic, detached from the world, at the same time extremely alien to the men of ordinary consciousness and despised by them. In Parvin's poetic sermon the dervish appears as the highest manifestation of human personality, the bearer of universal moral truths and at the same time deep mystical insights; thus, the poet engages every reader in the ongoing life of a centuries-old religious and mystical tradition.